2014
DOI: 10.1111/jipb.12218
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis transcriptional response to extracellular Ca2+ depletion involves a transient rise in cytosolic Ca2+

Abstract: Ecological evidence indicates a worldwide trend of dramatically decreased soil Ca(2+) levels caused by increased acid deposition and massive timber harvesting. Little is known about the genetic and cellular mechanism of plants' responses to Ca(2+) depletion. In this study, transcriptional profiling analysis helped identify multiple extracellular Ca(2+) ([Ca(2+) ]ext ) depletion-responsive genes in Arabidopsis thaliana L., many of which are involved in response to other environmental stresses. Interestingly, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Plants rapidly respond to a specific abiotic stress based on which type of sensor is stimulated, as this determines which series of responses is activated [ 193 , 194 ]. For instance, the sphingolipid glycosyl inositol phosphorylceramide (GIPC) is involved in sensing salt stress [ 195 ], REDUCED HYPEROSMOLALITY INDUCED CALCIUM INCREASE 1 (OSCA1) is an osmotic stress sensor [ 196 ], and CHILLING TOLERANCE DIVERGENCE 1 (COLD1) is a cold stress receptor [ 197 , 198 ].…”
Section: Mechanisms That Regulate Ccch Zinc-finger Proteins Under Abiotic Stressesmentioning
confidence: 99%
“…Plants rapidly respond to a specific abiotic stress based on which type of sensor is stimulated, as this determines which series of responses is activated [ 193 , 194 ]. For instance, the sphingolipid glycosyl inositol phosphorylceramide (GIPC) is involved in sensing salt stress [ 195 ], REDUCED HYPEROSMOLALITY INDUCED CALCIUM INCREASE 1 (OSCA1) is an osmotic stress sensor [ 196 ], and CHILLING TOLERANCE DIVERGENCE 1 (COLD1) is a cold stress receptor [ 197 , 198 ].…”
Section: Mechanisms That Regulate Ccch Zinc-finger Proteins Under Abiotic Stressesmentioning
confidence: 99%
“…Across ETC development Ca 2+ exerted greater control over the signaling and cell wall TC functional categories while auxin regulated a slightly higher number of ETC-specific DEGs encoding proteins involved in intracellular organization and nutrient transporter categories ( Table 3 ). In addition to the well described Ca 2+ signaling pathways regulating plant development ( Niu and Liao, 2016 ), a recent study has documented expression of genes encoding cell wall metabolizing enzymes positively regulated by Ca 2+ along with similar impacts on genes encoding nutrient transporters ( Wang et al, 2015 ). Similarly, as reported for other plant systems, auxin regulates expression of genes encoding proteins contributing to intracellular organization and to membrane transport of nutrients (e.g., Dai et al, 2009 ; Omelyanchuk et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional Ca 2+ -permeable cation channels belonging to the NSCCs, MSCCs, and VDCCs are likely able to take part of U uptake in roots. To support this hypothesis and the postulate of our approach (nutrient depletion inducing the upregulation of ion carriers and, then, an improved U uptake), previous transcriptomic analyses have shown that several genes coding Ca 2+ -permeable channels are upregulated in Arabidopsis plants starved with Ca, of which glutamate-like receptors (GLR1.2,1.4,2.5,2.8), annexins (ANN1,2,4,7), mechanosensitive ion channel proteins (MSL9,10) and cyclic nucleotide-gated ion channels (CNGC 9,11,19) (Table S4) (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data fromWang et al (2015) Arabidopsis transcriptional response to extracellular Ca 2+ depletion involves a transient rise in cytosolic Ca2+ . J Int Plant Biol 57,[138][139][140][141][142][143][144][145][146][147][148][149][150] …”
mentioning
confidence: 99%